THE INFLUENCE OF THE UZBEK LANGUAGE AMONG THE TURKIC PEOPLES TODAY - Zaripova Ma'mura Shaylovovna (Modern American Journals, 2025)
This article analyzes the influence of the Uzbek language among the Turkic peoples, its historical, cultural and social significance. The role of the Uzbek language in the family of Turkic languages, its distribution and interaction with other Turkic languages are examined. The article also discusses the role of Uzbek language in education, culture, business and communication.
Keywords: Uzbek language, Turkic languages, language reputation, language relations, cultural integration, linguistic impact